O era uma vez na ilustração: linguagem e plasticidade no universo gráfico de Rui de Oliveira - Mokarzel, Marisa de Oliveira (1998)
Study of the imagetic narrative that is processed in children's book illustrations, having as field of study the graphic production by Rui de Oliveira. Taking his illustrations as starting point, the figurative field has been studied, in which two main streams were observed: a relationship with the question of intelligibility and another with the esthetic question. When those two streams met the study of the narrative, they contributed with another type of observation: that of the illustration as language. For this observation to be possible, the examination of how the illustration is organized and is inter-related with other kinds of language was sought. The construction of the whole process of the study took into consideration the illustration's historic contextualization, the reach of an adequate methodology to the proposal, the support of theorists that would contribute with the questions related to the narrative, to the language and to the work's visual. After the analysis of this data the analysis of the drawing was possible. Throughout the analysis, there was the preoccupation about studying the questions of formal nature as well as the ones related to the meaning of the images inside the narrative chain. Since the illustrations were divided into three categories - the 1st in which the illustrator has the text as a reference; the second in which he constructs the text and image, and the third in which he narrates with images only - there was in a fist moment a more general observation, in which the illustrations belonged to the two first categories and it was observed that there was a connection with other kinds of language: visual and verbal. At a second instance, the illustrations of the third category were studied. This time the study was more specific: a single book was studied, and in this book all the steps to the construction of the imagetic narrative were observed. The stories in children's books told with images by Rui de Oliveira, made the perception of the mechanism of a language built with graphic elements possible.